2018
DOI: 10.1080/14756366.2018.1474878
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antitumour activities and molecular docking of thiocarboxylic acid ester-based NSAID scaffolds: COX-2 inhibition and mechanistic studies

Abstract: A new series of NSAID thioesters were synthesized and evaluated for their in vitro antitumor effects against a panel of four human tumor cell lines, namely: HepG2, MCF-7, HCT-116 and Caco-2, using the MTT assay. Compared to the reference drugs 5-FU, afatinib and celecoxib, compounds 2b, 3b, 6a, 7a, 7b and 8a showed potent broad-spectrum antitumor activity against the selected tumour cell lines. Accordingly, these compounds were selected for mechanistic studies about COX inhibition and kinase assays. In vitro C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Drugs that can act as multi-targeted agents can enhance efficacy and confront chemoresistance exhibited by GB cells. Thioesters has been investigated as an antitumor agent in multiple studies [40,41]. The present study validates potential of a novel orthothioester 5a, as an excellent pharmacological scaffold possessing strong cytotoxic, anti-angiogenic, and chemo-sensitization activity.…”
Section: Discussionsupporting
confidence: 72%
“…Drugs that can act as multi-targeted agents can enhance efficacy and confront chemoresistance exhibited by GB cells. Thioesters has been investigated as an antitumor agent in multiple studies [40,41]. The present study validates potential of a novel orthothioester 5a, as an excellent pharmacological scaffold possessing strong cytotoxic, anti-angiogenic, and chemo-sensitization activity.…”
Section: Discussionsupporting
confidence: 72%
“…We collected 259 COX-2 inhibitors from newly reported work to build an external test set, which included 44 highly active inhibitors (IC 50 ≤ 0.1 μM) and 215 weakly active inhibitors (IC 50 ≥ 10 μM). All these 259 inhibitors were different from the 2925 inhibitors in data set 1.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…But only recently have COXs, notably COX‐1, been connected to a wide range of human illnesses like cancer, heart failure, neurological, and neurodegenerative disorders. The molecular docking study revealed the importance of the thioester moiety for the interaction of the drugs with the amino acids in the active sites of COX‐2 [8] . The active site for COX‐1′s grid formation is thought to be the binding site for the crystal ligand diclofenac [9] .…”
Section: Introductionmentioning
confidence: 99%